Associations Between Divorce and Onset of Drug Abuse in a Swedish National Sample. Issue 5 (16th November 2017) - Edwards, Alexis C; Larsson Lönn, Sara; Sundquist, Jan; Kendler, Kenneth S; Sundquist, Kristina
Abstract: Rates of drug abuse are higher among divorced individuals than among those who are married, but it is not clear whether divorce itself is a risk factor for drug abuse or whether the observed association is confounded by other factors. We examined the association between divorce and onset of drug abuse in a population-based Swedish cohort born during 1965–1975 ( n = 651, 092) using Cox proportional hazards methods, with marital status as a time-varying covariate. Potential confounders (e.g., demographics, adolescent deviance, and family history of drug abuse) were included as covariates. Parallel analyses were conducted for widowhood and drug-abuse onset. In models with adjustments, divorce was associated with a substantial increase in risk of drug-abuse onset in both sexes (hazard ratios > 5). Co-relative analyses (among biological relatives) were consistent with a partially causal role of divorce on drug-abuse onset. Widowhood also increased risk of drug-abuse onset, although to a lesser extent. Divorce is a potent risk factor for onset of drug abuse, even after adjusting for deviant behavior in adolescence and family history of drug abuse. The somewhat less-pronounced association with widowhood, particularly among men, suggests that the magnitude of association between divorce and drug abuse may not be generalizable to the end of a relationship.